Harbouring brood lac: envisioning lac clusters. Issue 3 (3rd April 2022) - Chowdhury, Saurabh
ABSTRACT: This paper brings forth some of the major issues faced on the ground by traditional lac rearers and a particular grassroots initiative – Brood Lac bank, which seeks to address those concerns and facilitate sustainable lac-based livelihoods in Chhattisgarh. The idea of the Brood Lac Bank has been further extended to envision "Lac Clusters" which would not only sustainably produce lac but also add value though local processing, enabling rearers to produce raw industrial lac through local lac-based collectives/networks to directly engage with the market, evading multiple levels of middlemen that currently control the domestic lac economy.